Cholera: a relief or a development issue? - Ned Morgan; Brian Reed (2013)
WASH is often promoted as a way of preventing water borne diseases such as cholera. The overwhelming opinion is that the only sustainable way of preventing outbreaks is by decent water supplies, sanitation and hygiene behaviour, yet WASH actors do not appear to be active in the fight against the disease, with initial responses being led by medical issues. The concept of the disaster cycle should lead from relief to recovery to prevention, but the handover from emergency response to development is weak, made worse by the transfer of the lead agency from health to WASH, with differing priorities, actions and data needs. The idea of early recovery tries to bring “development” closer to the emergency response but this leads to blurred boundaries and ill-defined responsibilities. A stronger emphasis on prevention with clear practical actions would provide more focus for the eradication of this preventable disease.